Pemberdayaan Ekonomi Melalui Inovasi Pengelolaan Telur Asin Menjadi Bakpao di Dusun Penompo, Desa Sukosari Kecamatan Mantup Kabupaten Lamongan - Nanang Abdillah; Rahmat Rudianto; Zeini Fathihah Sari; Nabila Achfryl Choirunnisa; Aisyah Amanah Faticah; Fidaiyatul Millah; Khoirotun Nisya; Lailatuz Zuhriyyah; Nur Alfiyatul Lailiyah (Universitas Kristen Indonesia Toraja, 2025)
This research discusses economic empowerment assistance activities through innovation in the management of salted eggs into buns in Penompo Hamlet, Sukosari Village, Mantup District, Lamongan Regency. This activity was carried out with the aim of increasing local community income by utilizing local resources, namely salted eggs. In the process, training was provided to local business groups regarding processing and marketing techniques for salted egg-based buns using the Asset Based Community (ABCD) method. This method builds public awareness to be aware of the assets owned by the community. That it is important to achieve social change by raising awareness of the community itself by knowing their assets. The asset-based approach uses several strategies, including: Discovery (finding), Dream (dreaming), Design (designing), Define (determining), Destiny (ensuring). The results of this activity show an increase in participants' skills in processing salted eggs into more value-added products, as well as an increase in sales of bun products in the local market. Thus, this program has succeeded in having a positive impact on the economy of the Penompo Hamlet community and encouraging interest in micro-businesses in the area.)